Pengaruh Profitabilitas dan Leverage pada Nilai Perusahaan dengan Corporate Social Responsibility Sebagai Variabel Pemoderasi - Laksmi Dewi, Ni Made; Dharma Suputra, I Dewa Gede (E-Jurnal Akuntansi; Vol 28 No 1 (2019)DO - 10.24843/EJA.2019.v28.i01.p02, 2019)
The purpose of this study was to find out and obtain empirical evidence about the effect of profitability and leverage on firm value with Corporate Social Responsibility as a moderating variable. This study was conducted at mining companies listed on the Stock Exchange in 2015-2017. The number of samples taken was 14 companies with a number of research observations were 42 samples in 3 years, through nonprobability methods with purposive sampling technique. The analysis technique of this study used the Moderate Regression Analysis (MRA). Based on the results of the analysis it was found that profitability had a significant positive effect on firm value. Leverage had no significant negative effect on firm value . Corporate Social Responsibility strengthens the influence of profitability on corporate value. Corporate Social Responsibility weakens the influence of leverage on firm value. Keywords : Profitability, leverage, corporate social responsibility, corporate value.